2019
DOI: 10.1111/lam.13216
|View full text |Cite
|
Sign up to set email alerts
|

Extended spectrum beta‐lactamase producing Shiga‐toxin producing‐Escherichia coliin piglets, humans and water sources in North East region of India

Abstract: Significance and Impact of the Study: Multidrug resistant (MDR) enteric bacteria are global concern. Association of MDR traits in STEC isolates are another rising issue in human and animal health perspective. The interaction of such organisms among the human, domestic animals and adjoining water sources require to be analysed systematically. The present study exhibited the possible transmission of MDR-STEC among the human, domestic animals and water sources in the North eastern states of India. To the best of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Interestingly, E. coli isolates from unorganized farms exhibited higher resistance against majority of the commonly used antimicrobials in Mizoram. It may be due to overuse of antibiotics through self-medication, introduction of antimicrobial residues through swill feeding or even through environmental contamination, particularly contaminated water [4]. Most of the ESBLs producing organisms were also co-resistant to fluoroquinolones, aminoglycosides, and COT, which corroborates with the earlier findings [14], where the ESBLs producing enteric bacteria were found to be resistant to other groups of antibiotics including aminoglycosides, TE, sulfonamides, TR, and chloramphenicol.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Interestingly, E. coli isolates from unorganized farms exhibited higher resistance against majority of the commonly used antimicrobials in Mizoram. It may be due to overuse of antibiotics through self-medication, introduction of antimicrobial residues through swill feeding or even through environmental contamination, particularly contaminated water [4]. Most of the ESBLs producing organisms were also co-resistant to fluoroquinolones, aminoglycosides, and COT, which corroborates with the earlier findings [14], where the ESBLs producing enteric bacteria were found to be resistant to other groups of antibiotics including aminoglycosides, TE, sulfonamides, TR, and chloramphenicol.…”
Section: Discussionsupporting
confidence: 87%
“…An ESBL-producing E. coli possessing bla CTX-M and bla SHV associated with human diarrhea has been reported in India [12]. Puii et al [4] also reported the prevalence of ESBL producing genes (bla TEM , bla CTX-M , and bla CMY ) in the enteric bacteria of pig population in Northeastern India.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Regardless of the virulence of STEC strains, bacterial antimicrobial resistance (AMR) has emerged as a problem that threatens animal and public health globally. Indeed, STEC strains exhibiting multidrug‐resistant profiles to β‐lactams, phenicols, quinolones, aminoglycosides, trimethoprim/sulphamethoxazole and/or tetracyclines have been identified worldwide (Ahmed & Shimamoto, 2015; Colello, Krüger et al., 2018; Furlan et al., 2019; Mir & Kudva, 2019; Park et al., 2015; Puii et al., 2019). Although antimicrobials are not usually used in the treatment of STEC infections, the presence of antimicrobial‐resistant zoonotic bacteria in food has been documented, constituting a high risk of both human medicine and veterinary medicine, as the pool of genes from which pathogenic bacteria can acquire antibiotic resistance has increased (Poirel et al., 2018; Verraes et al., 2013), and can be easily exchanged between different bacterial species, in their hosts and in the environment (Kennedy et al., 2017).…”
Section: Introductionmentioning
confidence: 99%